Analisis Pendapatan Premi Dan Beban Klaim Terhadap Laba Pada PT Jasa Raharja Persero - Dwi Sri Wahyuni; Aris Munandar (Universitas Gorontalo, 2020)
The purpose of this article is to analyze the effect of premium income and claim burden on earnings at PT Jasa Raharja Persero Bima Representative with an associative research method approach. The population of this research is the insurance company PT Jasa Raharja Persero Bima Representative period 2010-2019. The technique of taking samples by purposive sampling with research samples used during the last 6 years. Data analysis method in this research is multiple linear regression analysis using IBM SPSS 21 software. The data used is secondary data obtained from PT Jasa Raharja Persero Representative Bima. This finding shows that partially there was no significant effect between premium income on earnings at PT Jasa Raharja Persero Representative Bima, Partial test there is a significant influence between the burden of claims on earnings at PT Jasa Raharja Persero Representative Bima, Simultaneous testing there is a significant influence between premium income and burden of claims on earnings at PT Jasa Raharja Persero Representative Bima.